THE DIGITAL ECONOMY: TRANSFORMATIONS, OPPORTUNITIES, AND CHALLENGES - Urunova Maftuna Gayratovna (Bright Mind Publishing, 2025)
The digital economy represents a paradigm shift in how goods and services are produced, distributed, and consumed, driven by advances in information and communication technologies. This article examines the key characteristics of the digital economy, including platformization, data-driven decision-making, and network effects. It analyzes the benefits—such as increased productivity, innovation, and market access—alongside the challenges, including digital divides, regulatory uncertainties, and cybersecurity risks. Through an exploration of global case studies and emerging trends, the article provides a comprehensive understanding of the digital economy’s potential to reshape industries and societies.
Keywords: Digital economy, platformization, big data, network effects, e-commerce, digital transformation, cybersecurity, regulatory frameworks, digital divide, innovation.